Lipid oxidation in biscuits: comparison of different lipid extraction methods - Patrignani, Mariela (2014)
This study was conducted in order to describe a proper method of extraction and quantification of peroxides in a complex matrix as biscuits. Different lipid extraction methods were applied in low lipid biscuits: direct solvent extraction; conventional Soxhlet extraction, the American Association of Cereal Chemists (AACC) method and a modification of the AACC method, in which the heating of the sample was avoided. Furthermore, the quantification method of peroxides was simplified and adapted to samples with low lipid content using easily accessible equipment. Significant differences (p ≤ 0.05) were found in the peroxide value of the lipids extracted with different extraction procedures. All the extraction methods performed, except the AACC, were found to be suitable for the determination of peroxides in low lipid biscuits. However, as direct solvent extraction provided a faster and simpler analysis, this method seemed to be the most suitable for peroxide determination in low lipid biscuits.